2007
DOI: 10.1016/j.pain.2007.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Influence of endometriosis on visceromotor and cardiovascular responses induced by vaginal distention in the rat

Abstract: This study examined pseudoaffective responses elicited by vaginal distention in urethaneanesthetized rats, and tested hypotheses that responses would be increased by endometriosis (ENDO) and vary with the estrous cycle. Three groups were studied: ENDO, shamENDO, and Naïve. ENDO was induced by autotransplantating small pieces of uterine horn (or, for shamENDO, fat) on mesenteric arteries. Ten weeks later, rats in proestrus or metestrus were anesthetized with urethane. Distendable latex balloons were inserted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
48
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 29 publications
8
48
0
Order By: Relevance
“…Our initial hypothesis was that proestrous-to-estrous changes in sensory innervation and cytokine content of the cysts, but not the uterine horn, contribute to proestrous-to-estrous differences in severity of ENDO-induced hyperalgesia (15,46). We did observe estrous changes in the cysts but not the uterine horn.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Our initial hypothesis was that proestrous-to-estrous changes in sensory innervation and cytokine content of the cysts, but not the uterine horn, contribute to proestrous-to-estrous differences in severity of ENDO-induced hyperalgesia (15,46). We did observe estrous changes in the cysts but not the uterine horn.…”
Section: Discussionmentioning
confidence: 72%
“…Like women with ENDO, rats with ENDO are subfertile (59). Once the cysts are fully developed, the rats also develop a vaginal hyperalgesia (15) that is accompanied by referred abdominal muscle hyperalgesia (46). In support of the clinical conclusion that ENDO is dependent on estrogens, the severity of both the vaginal and referred abdominal muscle hyperalgesia in rats varies with estrous stage in a manner that parallels estrous changes in circulating levels of estradiol.…”
mentioning
confidence: 91%
“…Obviously, the presence of PGP9.5-immunoreactive small nerve fibers in the functional layer of the endometrium in women with adenomyosis, uterine fibroids, and endometriosis is dependent on a common symptom of pain but not a disease itself. Because adenomyosis and uterine fibroids are believed to be under the control of the same steroid hormones as endometriosis, and also cause pelvic pain (15,26,27), it is indicated that PGP9.5-immunoreactive small nerve fibers in the functional layer of the endometrium may be involved in the mechanisms of pain generation in women with uterine fibroids and adenomyosis, and regulated by estrogen (12,(18)(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…For example, when treated by combined OCs and progestogens, endometriotic lesions, pain symptoms, and nerve fiber density in ectopic and eutopic endometrium and myometrium are decreased and the levels of estrogen are reduced (8,17). It is suggested that the innervation of the endometrium and myometrium and pain symptoms in women with endometriosis are under the control of estrogen (18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…These uterine transplants over time produce innervated and vascularized cysts (Berkley et al, 2004; 2005) and symptoms similar to women including vaginal hyperalgesia (Berkley et al, 2007; McAllister et al, 2009, 2012) referred abdominal muscle hyperalgesia (Giamberardino et al, 2002; Nagabukuro and Berkley, 2007), and bladder hyperactivity (Morrison et al, 2006). Therefore, we examined the relationships between vaginal hyperalgesia, cyst sensory and sympathetic innervation density, and peritoneal fluid levels of PGE2 and PGF2α 4-6wks after surgery when individual differences in hyperalgesic severity are greatest (McAllister et al, 2012).…”
Section: Introductionmentioning
confidence: 99%